Phone snubbing pada dewasa awal: Bagaimana peranan kontrol diri? - Nararrya Putri, Umi Laili; Niken Titi Pratitis; Isrida Yul Arifiana (INNER: Journal of Psychological Research, 2023)
Abstract The use of smartphones has now become a trend among children, adolescents, and early adults, who even tend to be excessive. Especially when individuals use smartphones regardless of the other person and the surrounding environment, which is called phubbing or phone snubbing. One of the factors that can affect phubbing is self-control, namely the ability to determine behavior such as changing, managing, and choosing behavior based on norms so that positive behavior is formed. The research aims to prove that there is a negative correlation between self-control and phubbing in early adulthood. The research was conducted using quantitative research methods using 2 psychological scales as measuring tools, namely the phubbing scale and the self-control scale. The research subjects used were 130 early adults who were taken using a non-probability sampling technique. Data analysis used the Spearman Rho technique. The results showed that the hypothesis was accepted, namely that there was a significant negative relationship between self-control and phubbing. The results obtained indicate that phubbing can be influenced by self-control. Keywords: Self-Control, Phubbing, Early Adulthood